Industry Concentration, Firm Size and Entry-Timing in Merger Waves - Lin Lin; Ngou Teng Pun; Zhongda He (Asian Academy of Management Journal of Accounting and Finance, 2023)
As early mover advantage and late mover advantage have been discussed for decades, the conditions for the best use of them are yet unclear. Using the U.S. merger data during 2000–2019, this study examines the entry-timing and the post-merger performance of 1,376 bidders in the merger waves recognised. We find that early movers have advantages with higher post-merger performance in a merger wave, while the effect of late mover advantage is not significant. Moreover, early mover advantage can only be implemented in competitive industries. Our analysis further provides the entry-timing strategies for large firms and small/mid enterprises, respectively. Our results indicate that late mover advantage can only be adopted in large companies, while small/mid firms should be followers, not early or late movers, in high concentration industries. Overall, our study sheds new light on the entry-timing in a merger wave with the consideration of different market concentration environment and different firm size.